2014
DOI: 10.1016/j.actpsy.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The association between children's numerical magnitude processing and mental multi-digit subtraction

Abstract: Children apply various strategies to mentally solve multi-digit subtraction problems and the efficient use of some of them may depend more or less on numerical magnitude processing. For example, the indirect addition strategy (solving 72-67 as "how much do I have to add up to 67 to get 72?"), which is particularly efficient when the two given numbers are close to each other, requires to determine the proximity of these two numbers, a process that may depend on numerical magnitude processing. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…In later years, the application of the written algorithm could be less systematic and more adaptively selected as a function of the characteristics of the problems. One argument for this scenario is the fact that the ability to represent the magnitude of numbers, a central aspect of basic number sense which sharpens through development (Halberda & Feigenson, 2008), is particularly linked to the flexible use of mental calculations (Linsen, Verschaffel, Reynvoet, & De Smedt, 2014, 2015.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…In later years, the application of the written algorithm could be less systematic and more adaptively selected as a function of the characteristics of the problems. One argument for this scenario is the fact that the ability to represent the magnitude of numbers, a central aspect of basic number sense which sharpens through development (Halberda & Feigenson, 2008), is particularly linked to the flexible use of mental calculations (Linsen, Verschaffel, Reynvoet, & De Smedt, 2014, 2015.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…These tests reflect performance averaged across various mathematical skills and it has been observed that numerical processing impacts more on some specific mathematical skills compared to others. For example, Linsen, Verschaffel, Reynvoet, and De Smedt (2014) showed that in multi-digit subtraction, the use of the flexible subtraction-by-addition strategy relied more on numerical processing than the more common direct subtraction strategy (see also Fuchs, Geary, Fuchs, Compton, & Hamlett, 2014;Jordan, Mulhern, & Wylie, 2009).…”
mentioning
confidence: 98%
“…Linearity is initially acquired for smaller ranges and progressively, with age and increasing number knowledge, linearity is extended to larger ranges (Berteletti et al, 2010; Siegler and Booth, 2004; Siegler et al, 2009). Performance on the NL task correlates with other estimation tasks (Booth & Siegler, 2006; Laski & Siegler, 2007), improves following interventions on children's linear and cardinal understanding of the numerical sequence (Ramani and Siegler, 2008; Siegler and Ramani, 2008), and is correlated with and is predictive of arithmetic learning and mathematical achievement (Booth & Siegler, 2008; Link, Nuerk, & Moeller, 2014; Linsen, Verschaffel, Reynvoet, & De Smedt, 2014; Ostergren & Träff, 2013; Sasanguie, Göbel, Moll, Smets, & Reynvoet, 2013; Schneider, Grabner, & Paetsch, 2009). Performance is also impaired or delayed in children with math learning difficulty (Geary et al, 2008; Landerl, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Importantly, improving children's performance on the NL task enhances performance in numerical magnitude processing tasks as well as facilitates learning of multi-digit addition problems (Booth and Siegler, 2008; Kucian et al, 2011). Because the NL task has been shown to be a strong and unique predictor of arithmetical ability in grades 1 and 2 over and above other non-symbolic and symbolic tasks (Lyons et al, 2014), and because the NL tasks were correlated to mental multi-digit subtraction performance (Linsen et al, 2014), it can be argued that the NL task is specifically calling upon numerical processes that are crucial for later acquisition of mathematical competences. Two types of functional processes involved in the number line task might explain the relationship with mathematical performance and in particular with subtraction problems.…”
Section: Introductionmentioning
confidence: 99%